DAKWAH BERBASIS BUDAYA LOKAL STUDI IMPLEMENTASI NASKAH PENGOBATAN FUADI AMRI DI KECAMATAN KELUMBAYAN KABUPATEN TANGGAMUS - Sari, Jenila; Shonhaji, Shonhaji; Yanti, Fitri (Universitas Islam Negeri Raden Intan Lampung, 2021)
Da'wah is an effort to invite, convey, and spread the truth to the community to carry out the teachings of Islam according to the guidance of the Qur'an and the Sunnah of the Prophet Muhammad SAW. The cultural da'wah approach in the form of Medical Manuscripts is carried out in the Kelumbayan District community who still carry out the Hindu-Buddhist tradition. This study aims to reveal the implementation of Fuadi Amri's treatment script in Kelumbayan District and the results. This research is a qualitative descriptive field research. Data sourced from primary data and secondary data. Data collection techniques consist of interviews, observations, and documentation, as well as data analysis by collecting data, data reduction, data presentation, and conclusions. The results of the research on the implementation of the treatment script carried out by Fuadi Amri in Kelumbayan District were a process of deliberation, providing advice and guidance, instructing patients and their families to do dhikr and prayer, and provide final motivation. The result of the implementation of the Medical Manuscript is the achievement of the goals of da'wah both practical, realistic, and idealistic. Preservation of local culture with its usefulness, as well as uniting a multicultural society.